Impact of orientational distribution of adsorbing objects on dynamics of Random Sequential Ballistic Adsorption (RSBA) dynamics - Shelke, Pradip B.; Banpurkar, Arun G.; Ogale, Satishchandra B.; Limaye, A. V. (Surface Science, 2007)
Recently, by proposing a new variant of Random Sequential Adsorption (RSA) namely Random Sequential Ballistic Adsorption (RSBA) model [Pradip B. Shelke, A.G. Banpurkar, S.B. Ogale, A.V. Limaye, Surf. Sci. 601 (2007) 274], we addressed the issue of adsorption dynamics of extended objects where the objects, upon adsorption, protrude outside the substrate. This study brought out the role of the arriving trajectory in the adsorption dynamics. In the present work the possible role of the orientational distribution of the arriving objects in the RSBA dynamics is investigated. The dynamics of RSBA of needles (line segments) is studied analytically and by computer simulation for different types of theta distributions of arriving needles, theta being the angle made by the arriving needle with normal to the substrate. Three types of theta distributions, namely a uniform distribution over the range (0, pi/2), a Gaussian distribution and a distribution uniform over the solid angle, are considered. Analytical treatment establishes that in all the three cases, the number n(t) of adsorbed objects at a late time t follows a power law n(t) similar to t(alpha), and the exponent a depends on the specifics of the theta distribution. In general, for distribution f(theta) proportional to theta(beta), for theta -> 0, alpha is found to be 2/(beta + 3). The simulation results are in excellent agreement with the analytical findings and together they reveal that the orientational distribution of arriving objects has significant consequences for the Random Sequential Ballistic Adsorption (RSBA) process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Adsorption; adsorption kinetics; Monte Carlo simulations; random sequential adsorption (RSA)

Interface and defect structures in YBa(2)Cu(3)O(7-delta) and Nb : SrTiO(3) heterojunction - Fu, Lian-feng; Browning, Nigel D.; Ramadan, W.; Ogale, Satishchandra B.; Kundaliya, D. C.; Venkatesan, T. (Journal of Physics D-Applied Physics, 2007)
YBa(2)Cu(3)O(7-delta) thin films grown on a Nb-doped SrTiO(3) substrate by a pulsed laser deposition method have been fully characterized by scanning transmission electron microscopy Z- contrast imaging and electron energy loss spectroscopy techniques. The Nb distribution was found to be uniform and unchanged across the interface, ensuring a high quality p - n junction heterointerface. We first observed the coexistence of 124 and 125 YBCO defect structure phases, appearing as planar defects in a YBCO thin film. Dispersive Y(2)O(3) nanoparticles have also been observed in the thin film. The interaction of these defect structures and Y(2)O(3) nanoparticles is thought to be beneficial for pinning flux through the entire film thickness.

Investigation of wustite (Fe1-xO) by femtosecond laser assisted atom probe tomography - Bachhav, Mukesh N.; Danoix, R.; Danoix, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Vurpillot, F. (Ultramicroscopy, 2011)
In this paper, we report results obtained from laser assisted three-dimensional (3-D) atom probe tomography (APT) on wustite (Fe1-xO). Oxides are generally insulating and hence hard to analyse in conventional electrical assisted APT. To overcome this problem, femtosecond laser pulses are used instead of voltage pulses. Here we discuss some aspects of pulsed laser field evaporation and optimization of parameters to achieve better chemical accuracy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Atom probe tomography; Laser assisted field evaporation; Wustite

Isobutrin from butea monosperma (flame of the forest): a promising new natural sensitizer belonging to chalcone class - Agarkar, Shruti A.; Kulkarni, Roshan R.; Dhas, Vivek V.; Chinchansure, Ashish A.; Hazra, Partha; Joshi, Swati P.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2011)
In this work, ``isobutrin'', an ecofriendly sensitizer that is extracted from Butea monosperma (commonly known as ``Flame of the Forest'') flowers, is introduced. It is a bright yellow pigment belonging to the chalcone class and is examined as a sensitizer for optoelectronic applications. It is observed that chelation of this dye with Ti ions results into a strong dye-TiO(2) charge transfer (DTCT) band in the visible region. This Ti-Isobutrin chelate is stable, irreversible and its formation is studied using Benesi-Hildebrand plot. The locations of HOMO-LUMO states of the Ti-isobutrin chelate and the corresponding band alignment with TiO(2) are obtained. Also, a thermal stability test revealed that isobutrin is stable above 100 degrees C.
Keywords: Butea monosperma; chalcone; dye-sensitized solar cell; isobutrin; sensitizer; TiO(2)